Estudio de factibilidad para la implementación de una planta procesadora de macerado de membrillo en la Parroquia de Bayushig - Merino Caluña, Diego Geovanny (2022)
This research project was carried out to carry out a feasibility study for implementing a quince maceration processing plant in the parish of San Antonio de Bayushig, Penipe canton, province of Chimborazo. The purpose was to know the existence of macerated production, to improve its price and quality for the benefit of the small producers of the parish. During our market study allowed us to identify the existing raw material in the sector, it was determined the great productive potential that the bushing and Penipe areas have, the same ones that produce very good quality fruit to meet the needs of the local and national market that has a consumption population of 777.06 with the acquisition of quince maceration of 27,585.57 liters per year with an objective demand of 10,482.52.Within the feasibility study, the following indicators were obtained: the NPV that during five years proved as a result 4,706.27 and according to this result the Internal Rate of Return is 7.06%, the Cost-Benefit was 1.40 being more significant than one and existing a profit of 0.40; finally, the economic investment made within the useful life of the project is recovering; therefore, it is feasible to conduct the present research study